2015
DOI: 10.1007/s00170-014-6613-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study on hydroforming characteristics of friction stir welded aluminum alloy tubes

Abstract: Friction stir welding (FSW), as a solid state joining technique, has emerged as an efficient method for manufacturing tailor-welded blanks to optimize weight or performance in the final component. As the basic design of lightweight frame structures in the automotive and aircraft industry is frequently based on tubular profiles, the joining strategies and forming technologies have to be developed accordingly. In the present study, FSW tube was produced by a novel processing sequence. The plastic deformation cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The thickness distribution greatly depends on the sequence of the contacting die and the variations of the curvature radius of the tube during hydroforming. Moreover, the weld shows an inhibitory effect for the generation of the wrinkles and decreases the number of the wrinkles as compared to the seamless tube during hydroforming [57].…”
Section: Aluminum Alloy Behavior During Hydroforming Processmentioning
confidence: 98%
“…The thickness distribution greatly depends on the sequence of the contacting die and the variations of the curvature radius of the tube during hydroforming. Moreover, the weld shows an inhibitory effect for the generation of the wrinkles and decreases the number of the wrinkles as compared to the seamless tube during hydroforming [57].…”
Section: Aluminum Alloy Behavior During Hydroforming Processmentioning
confidence: 98%
“…The hydro-formability of friction stir-welded (FSW) aluminum alloy tubes is investigated, and the hydroforming performance of the FSW tubes was mainly investigated by die-bulge forming with fixed ends. It is found that hydro-forming FSW aluminum alloy tubes is a new deal and does show a few peculiarities [15]. A tube bulging test was proposed, and the theory was introduced.…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet the demand of the fuel efficiency and emission reduction, aluminum alloy is widely used in the aerospace and automobile industries for its advantages of high strength-to-weight ratio, excellent corrosion resistance, and good weldability [1][2][3]. However, it is difficult for the aluminum alloy to form a complex shape part due to the poor formability at room temperature.…”
Section: Introductionmentioning
confidence: 99%